The value of a third year in upper secondary vocational education - Evidence from a piloting scheme - Erika Ekström (Institute for Labour Market Policy Evaluation (IFAU), 2002)
The 1991-reform of upper secondary school, in which the two-year vocational programmes were transformed into three-year programmes, was implemented all over the country in 1995/96. The reform was piloted in the final years of the 1980s. The pilot scheme is an example of a natural experiment. Expressed in a simple way, students who applied to upper secondary school in 1990 either lived in a pilot municipality with a possibility to choose a three-year vocational programme instead of a two-year or in a non-pilot municipality with only two-year vocational programmes. In this paper I estimate the effect of living in a pilot municipality in 1990 on three outcomes: years of upper secondary education, university enrolment and the rate of inactivity. My results suggest positive effects on years of upper secondary education for those who lived in a pilot municipality in 1990. One of the important changes was that the third year in upper secondary vocational education gave individuals general eligibility to continue to higher education. However, the third year did not have a statistically significant effect on the probability to continue to higher education, at least not within six years after completing upper secondary education.
Keywords: I21; 330; Vocational education; upper secondary education; natural experiment